Associations between match participation, maturation, physical fitness, and hormonal levels in elite male soccer player U15: a prospective study with observational cohort - Ebrahim Eskandarifard; Hadi Nobari; Filipe Manuel Clemente; Rui Silva; Ana Filipa Silva; Antonio José Figueiredo (BMC, 2022)
Abstract Objectives The aims of this study were to analyze the relationships between minutes of play (MP) and maturity status, fitness, and hormonal levels and to explain how those measures influence the time of play. Methods Twenty-six youth soccer players U15 participated in this study over a full-season period. Anthropometric measures, maturity status, growth hormone (GH), insulin-like growth factor and physical levels such as maximal oxygen uptake (VO2max), fatigue index, countermovement jump (CMJ) performance were collected. At the end-season, players were assessed in 6 different tests over four days. Results VO2max largely correlated with GH (r = 0.57) and CMJ (r = 0.51). Also, GH largely correlated with CMJ (r = 0.55). MP had moderate correlations with VO2max (r = 0.44) and CMJ (r = 0.42). Multiple linear regression with maturation, physical fitness and hormonal levels explained R2 of 0.62 of the MP (F (8, 17) = 3.47, p = 0.015). Although each independent variable alone was not able to determine the playing time, when using the interactions, the model significantly explained the MP. Conclusions The combination of maturity status, physical fitness, and hormonal levels seem to play a determinant role in explaining the match participation in youth soccer players.